THE INFLUENCE OF USING DOMINO LEARNING MEDIA ON THE UNDERSTANDING OF MATHEMATICAL CONCEPTS IN ADDITION MATERIAL AMONG SECOND GRADE STUDENTS OF SD INPRES BAKUNG, GOWA REGENCY : Makasar, Indonesia - Fatmawati; Patta, Rahmawati; Hotimah; Eka Putri Atjo, Samsuryani (Universitas Muhammadiyah Bengkulu, 2025)
This research aims to describe the use of domino learning media in mathematics lessons, assess students' understanding of mathematical concepts in addition, and examine the effect of using domino learning media on the mathematical concept comprehension of second-grade students at SD Inpres Bakung, Gowa Regency. This study is an experimental research with a quantitative approach. The research design employed is a quasi-experimental type with a Pretest-Posttest Control Group Design. The population consists of all second-grade students at SD Inpres Bakung, Gowa Regency. The sample includes 15 students in the experimental group and 15 students in the control group, selected through purposive sampling. Data were collected using observation sheets to monitor the implementation of the learning media and student achievement tests. Data analysis involved descriptive and inferential statistics. The descriptive analysis showed that the implementation of the learning process using domino media from the first to the third meeting was categorized as very good. This indicates that the improvement in students' understanding of mathematical concepts in addition was better in the experimental group compared to the control group. This is supported by the higher average posttest scores of the experimental group compared to the control group.In conclusion: (1) the learning process assisted by domino learning media was very effective, (2) test results revealed an improvement in students’ understanding of mathematical concepts related to addition, and (3) using domino learning media significantly influenced the comprehension of mathematical concepts in addition among second-grade students at SD Inpres Bakung, Gowa Regency. Keywords: Domino Learning Media, Mathematical Concept Comprehension (Addition).